A cellular analysis of meristem activity at the end of flowering points to cytokinin as a major regulator of proliferative arrest in Arabidopsis - Merelo, Paz; González-Cuadra, Irene; Ferrándiz, Cristina (Current biology, 2022)
In monocarpic plants, all reproductive meristem activity arrests and flower production ceases after the production of a certain number of fruits. This proliferative arrest (PA) is an evolutionary adaptation that ensures nutrient availability for seed production. Moreover, PA is a process of agronomic interest because it affects the duration of the flowering period and therefore fruit production. While our knowledge of the inputs and genetic factors controlling the initiation of the flowering period is extensive, little is known about the regulatory pathways and cellular events that participate in the end of flowering and trigger PA. Here, we characterize with high spatiotemporal resolution the cellular and molecular changes related to cell proliferation and meristem activity in the shoot apical meristem throughout the flowering period and PA. Our results suggest that cytokinin (CK) signaling repression precedes PA and that this hormone is sufficient to prevent and revert the process. We have also observed that repression of known CK downstream factors, such as type B cyclins and WUSCHEL (WUS), correlates with PA. These molecular changes are accompanied by changes in cell size and number likely caused by the cessation of cell division and WUS activity during PA. Parallel assays in fruitfull (ful) mutants, which do not undergo PA, have revealed that FUL may promote PA via repression of these CK-dependent pathways. Moreover, our data allow to define two phases, based on the relative contribution of FUL, that lead to PA: an early reduction of CK-related events and a late blocking of these events.